(untitled) (Gestión y Gerencia, 2020)
The research diagnoses the operation of the virtual currency Bitcoin as a means of payment in electronic commerce. It also analyzes the relationship between virtual currency and electronic commerce, describes the operation of this virtual currency in the commercial modality and determines the strengths and weaknesses of the use of this currency as a means of payment in electronic commerce. The study is descriptive and documentary. The data collection was carried out through an observation guide, whose documentary sources are: the virtual wallet Blockchain, the World Trade Organization and the MarketerDaily website. Concludes that the relationship between the use of Bitcoin and electronic commerce is narrowing, due to the accelerated technological advance of the Internet; which most visible consequence is the digitalization of processes for obtaining goods and services, reducing the costs of commercial transactions. The Bitcoin streamlines and facilitates transactions between customers and companies, minimizes the time to make transactions effective, with lower rates and without any intervening entity. It is an attraction for those who market in such electronic activity, but due to its high volatility, it generates uncertainty